Mi’kmaw-Owned Partnership in Clearwater Seafoods - Doucette, Mary; Stack, Ryan (Journal of Aboriginal Economic Development)

(untitled) (CANDO, 2024)
The keynote presentation at the 2023 Cando Annual Conference told of the Mi’kmaw Coalition and Premium Brand Seafoods’ acquisition of Clearwater Seafoods. It provided a Mi’kmaw corporate perspective of the acquisition and was co-presented by Mike McIntyre (Membertou CFO), Jenny Morgan (Clearwater Seafoods LP), and Darryl McDonald (Paqtnkek Mi’kmaw Nation CAO). The following is a summary of their presentation, focusing on three core aspects of the deal: building business relationships, minimizing risks to preexisting community assets, and highlighting opportunities for Clearwater to expand through strategic innovation. Finally, although Premium Brands was not represented in the presentation, examining their role in the partnership highlights the potential for strategic innovation in the future.